Efek Stres terhadap False Memory Recall dan Recognition - Nurwanti, Ratri; Permatasari, Dian Putri; Fitria, Ika; Ahmad, Zakki Munawar; Anggraini, Yohana Dwivi (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
Memory is often thought of as a video recorder that can record and store events precisely as they occur. Whereas in addition to being constructive, memory is also reconstructive, which means that memory can change due to certain conditions, resulting in false memories. The effect of stress on false memory was tested in this between-subject design experiment.  Participants in this study (N = 38) were divided into two conditions through a random assignment process, control conditions (N = 27) and stress or experiment conditions (N = 11).  We used a modified Trier Social Stress Test-Group to induce stress and Deese-Roediger-McDermott Paradigm to measure false memory. The independent sample t-test showed that there was no significant difference on false memory recall and false memory recognition between participants in the experiment condition and participants in the control condition. This indicated that stress did not affect false memory. The implications of this finding are the importance of replicating similar studies investigating stress induction in various stages of memory processing and forms of stress induction to produce a more precise understanding of the stress and false memory mechanism.